Mind the gap: Revisiting the concentration index for overweight - David Madden (University College Dublin, UCD School of Economics, 2017)
Much analysis of the socioeconomic gradient of overweight/obesity has involved the calculation of concentration indices for the incidence of these conditions. However this analysis ignores the severity of the conditions, in particular whether there is a gradient to how far are people above the relevant thresholds. Calculation of the concentration index for severity based measures for a dataset for Ireland reveals a much stronger gradient than for the incidence based measures. It is recommended that analysis of severity should always accompany analysis of the incidence of overweight/obesity.
Keywords: I14; I32; 330; Overweight; obesity; socioeconomic gradient; concentration index